Physicochemical Analysis, Identification and Characterization of drug Irbesartan and Triamterene - Motiwale, Abhijeet; Singh Sengar, Narendra Pratap (Journal of Neonatal Surgery, 2025)
The study paper focuses on the physicochemical analysis and structural elucidation of two pharmacologically important compounds: Irbesartan, an angiotensin II receptor antagonist, and Triamterene, a potassium-sparing diuretic. The identification and characterization were carried out using various analytical and spectroscopic techniques including UV-Visible spectroscopy, FTIR (Fourier Transform Infrared Spectroscopy), and melting point determination. Organoleptic properties such as color, odor, and appearance were also assessed. The λmax of both drugs was determined in appropriate solvents to establish their UV absorption profiles. FTIR analysis confirmed the presence of functional groups characteristic to each drug, providing molecular fingerprint confirmation. Melting point analysis further supported the purity and identity of the samples. These characterization studies are essential for ensuring the quality, efficacy, and safety of pharmaceutical formulations containing Irbesartan and Triamterene, and they provide a strong foundation for further formulation development and quality control.